A QUALITATIVE SYNTHESIS OF THE NATURE OF PUBLIC ADMINISTRATION AND MANAGEMENT IN DEMOCRATIC SOUTH AFRICA SINCE 1994 AND BEYOND - Bogopane, Lebosa Peter (European Scientific Journal, ESJ, 2015)
This manuscript attempted to describe the wax and the eventual wane of the government’s efforts to increase the level of public participation in the public administration and management structures, systems, processes and the procedures. The ultimate intent being to enhance and consolidate the role of active public participation in good governance and effective/efficient service delivery throughout the country. These and other similar, issues, problems, and challenges are ones that have inspired and motivated the author to undertake this research discourse. Subsequently, it has been the intention of this article to provide a qualitative synthesis and analysis of the nature of public administration and management in Mzansi (South Africa) since1994, and beyond. To achieve this, the study started by identifying five themes/principles of a duly functional public administration/management, namely :(1) considering the public as citizen;(2) treating public as customer; (3) looking at the public as partner;(4) noting the public as voter; and (5) accepting the public as tax payer, and used them as the basis for this analytic synthesis. From these guiding themes/principles, this paper adopted qualitative data collection methods such as (participant observation, in-depth interviewing, qualitative document study, and qualitative case study) and qualitative data analysis and interpretation techniques such as (content analysis and qualitative case study analysis) were used to collect the required pertinent data and to analyse and interpret it accordingly. Qualitative nonprobability judgmental sample technique was preferred and used to determine the sample of the study. Subsequent to the key research problem and its accompanied sub-problems underlying the study, along with the research questions and related research objectives identified, several findings were arrived at and recommendations were suggested on the basis of the findings thus far arrived at.